IMPLEMENTASI KURIKULUM MERDEKA PADA PEMBELAJARAN PAI - Iqtianti, Haniefah; Sari, Dwi kurnia; Yunita, Tiara; Wati, Flora Ambar; anisak, Siti darojatun; Rofiq, Ahmad Ainur; Ali, M. Makhrus; pengelola, pengelola (Tasyri` : Jurnal Tarbiyah-Syari`ah-Islamiyah, 2025)
Islamic Religious Education is oriented towards forming students who have an Islamic personality and are devoted to Allah SWT, therefore Islamic Religious Education facilitates students to learn and actualize all their physical and spiritual potential. The learning in the independent curriculum is carried out flexibly so that students and educators can be independent, where educators can adapt the materials, methods and learning strategies to the needs of students and school characteristics. This learning is carried out with Intracurricular learning and also Co-curricular learning. In implementing PAI learning in the independent curriculum, there are two duties of PAI Teachers, namely PAI Teachers who teach PAI lessons in intracurricular learning and PAI Teachers as accompanying teachers in project-based co-curricular learning. This research aims to analyze the application of PAI learning in the Independent Curriculum